Brazing method to join a novel Cu54Ni6Zr22Ti18 bulk metallic glass to carbon steel. (17th November 2017) - Kim, Jonghyun; Lee, Taekyung
ABSTRACT: This study joined a novel Cu-based bulk metallic glass (BMG) to carbon steel using a brazing process. Cu54 Ni6 Zr22 Ti18 BMG was brazed to SS400 carbon steel using filler metal at 713 K under a compressive stress of 15 MPa for 3 min. Considering the relatively low glass-forming ability, pure Zn and Zn–Ag–Al filler metals were selected to suppress the crystallisation during a reheating thermal cycle. A sound bonding interface without notable chemical diffusion was obtained using the suggested brazing method, particularly with the Zn–Ag–Al filler. This gave rise to considerable improvement in shear bonding strength, from 9 to 45 MPa, when replacing the Zn filler with the Zn–Ag–Al filler. The present method also induced no marked change in phase composition of the BMG due to the low bonding temperature and short bonding time. Slight variations in glass transition temperature and crystallisation temperature would result from a thermal annealing effect.